NEUROD1 is highly expressed in extensive-disease small cell lung cancer and promotes tumor cell migration. (August 2020) - Ikematsu, Yuki; Tanaka, Kentaro; Toyokawa, Goji; Ijichi, Kayo; Ando, Nobuhisa; Yoneshima, Yasuto; Iwama, Eiji; Inoue, Hiroyuki; Tagawa, Tetsuzo; Nakanishi, Yoichi; Okamoto, Isamu
Highlights: We performed IHC analysis of ASCL1 and NEUROD1 expression in SCLC clinical samples. The expression pattern of ASCL1 and NEUROD1 differs between LD- and ED-SCLC. NEUROD1 expression is higher in ED-SCLC than that in LD-SCLC. NEUROD1 promotes the migration of SCLC cells in vitro. NEUROD1 might thus contribute to metastasis in ED-SCLC. Abstract: Introduction: Small cell lung cancer (SCLC) manifests high-grade neuroendocrine features, and the transcription factors ASCL1 and NEUROD1 play an important role in the survival and growth as well as contribute to the heterogeneity of SCLC cells. The relative abundance of ASCL1 and NEUROD1 mRNAs differs among human SCLC cell lines, but the expression pattern of the encoded proteins in clinical SCLC specimens and its relation to clinicopathologic characteristics of patients have been unclear. Materials and Methods: We retrospectively analyzed tumor specimens collected from 95 previously untreated SCLC patients between June 1988 and December 2017 for ASCL1 and NEUROD1 expression by immunohistochemical staining. We also examined the effects of overexpression or depletion of NEUROD1 on cell migration in SCLC cell lines. Results: Overall survival did not differ significantly between SCLC patients with a high or low expression score for ASCL1 or NEUROD1 in their tumor samples. The staining score for NEUROD1 was significantly higher in extensive-disease (ED) samples than in limited-disease (LD) samples (median of 160 versus 80 out of a maximum of 300, P  =  0.0389), and the proportion of tumors with an ASCL1 high NEUROD1 low phenotype was smaller for ED-SCLC. Overexpression or depletion of NEUROD1 in SCLC cell lines promoted or attenuated cell migratory activity, respectively. Conclusion: Our clinical and experimental data indicate that the expression of NEUROD1 is increased in ED-SCLC and promotes the migration of SCLC cells. NEUROD1 might thus contribute to metastasis in ED-SCLC.